Determining the Relationship Between Water Quality and Ulcerative Mycosis in Atlantic Menhaden - Noga, Edward; Johnson, Stephen; Dickey, David; Daniels, Deborah; Burkholder, JoAnn; Stanley, Donald (East Carolina University, 1993)
The objectives of this study were to investigate the possible causes of ulcerative mycosis (UM) in the Albemarle-Pamlico Estuary. Ulcerative mycosis is the commonest disease affecting the finfish populations of the Albemarle-Pamlico Estuary. While infectious agents have been isolated from UM lesions, the underlying environmental cause of the disease remains a mystery. We presently know very little of how water quality (including pollution) influences UM prevalence. The difficulty in reproducing the disease by simply challenging fish with the fungal pathogen suggests that environmental stress may play a very important role in disease development. Previous sampling surveys for UM that simultaneously examined water quality did not always show any consistent relationship to disease prevalence, perhaps because water quality monitored simultaneously with disease sampling may not be representative of the actual conditions that caused the disease outbreak. To obtain more reliable data on the risk factors influencing the development of UM, we placed clinically normal Atlantic menhaden in tanks at various sites along the Albemarle-Pamlico Estuary and examined them periodically for the development of UM lesions. We also simultaneously measured ambient water quality, including dissolved oxygen, salinity, temperature, pH, ammonia, nitrite, chlorophyll a, and prevalence of a new toxic dinoflagellate that we have recently discovered in the Albemarle Pamlico Estuary.
Project No. 92-15. ICMR Tech Report 93-08. The research on which the report is based was supported in part by the United States Environmental Protection Agency and the North Carolina Department of Environment, Health, and Natural Resources (EHNR), through the Albemarle-Pamlico Estuarine Study. Contents of the publication do not necessarily reflect the views and policies of the United States Environmental Protection Agency, the North Carolina Department of Environment, Health, and Natural Resources, nor does mention of trade names or commercial products constitute their endorsement by the United States or North Carolina Government.